Hydrochoric Seed Dispersal of Riparian Plants Follows Hydrological Patterns Closer Than Geomorphic Variation - Jacqueline H. T. Hoppenreijs; R. Lutz Eckstein; Xiaolei Su; Christer Nilsson; Lina E. Polvi; Lovisa Lind (Ecosystems, 2025)
Water is an important dispersal vector for seeds of riparian plants, but little is known on how this form of dispersal, called hydrochory, varies throughout seasons and through geomorphically different areas. Therefore, we trapped seeds in 25 x 25 Astroturf mats along a free-flowing boreal river for an entire year. Sites mirrored the full range of geomorphic variation in the area and traps were emptied before and after the annual peak flow. The traps collected 2,062 seeds before the spring flood and 16,157 during the spring flood. While most of the seeds were deposited in the summer-low water traps (from now on “water edge”) before the spring flood, they were distributed more equally in the riparian traps (defined as the level 40 cm above the water edge; from now on “riparian zone”) during the spring flood. We found 77 species in total, of which 71 were at least recorded during the spring flood. Species numbers were higher at the water edge than at the riparian zone before and during the spring flood. Only 6.6% of the seeds, from 26 species, were viable. Most viable seeds were found in the water edge traps and, during the spring flood, in the riparian zone traps. While species that are primarily dispersed by water were not the most abundant among the viable seeds, they were the most species-rich group. This means that hydrochory is an important dispersal mechanism for riparian vegetation and an important contributor to riparian plant diversity in free-flowing rivers, and that changes in flow regimes, such as by flow regulation, can affect riparian vegetation composition.